2009
DOI: 10.1007/s00477-009-0304-4
|View full text |Cite
|
Sign up to set email alerts
|

A method for reliability-based optimization with multiple non-normal stochastic parameters: a simplified airshed management study

Abstract: We develop methodologies to enable applications of reliability-based design optimization (RBDO) to environmental policy setting problems. RBDO considers uncertainty as random variables and parameters in an optimization framework with probabilistic constraints. Three challenges in environmental decision-making problems not addressed by current RBDO methods are efficient methods in handling: (1) non-normally distributed random parameters, (2) discrete random parameters, and (3) joint reliability constraints (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The corresponding dispersion coefficient values from Table 5 are also available. The existence of discrete variables in the Gaussian dispersion model means that a probabilistic constraint will be formulated as Bayesian conditional probability such that continuous distributions are used to approximate the distributions of a, c, d, f as discussed in Chan et al (2010).…”
Section: Dispersion Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding dispersion coefficient values from Table 5 are also available. The existence of discrete variables in the Gaussian dispersion model means that a probabilistic constraint will be formulated as Bayesian conditional probability such that continuous distributions are used to approximate the distributions of a, c, d, f as discussed in Chan et al (2010).…”
Section: Dispersion Coefficientmentioning
confidence: 99%
“…In this work we focus on the air pollution of on-road vehicles to the extent that transportation policies can be evaluated using novel engineering optimization techniques. Similar attempts in policy-setting exist in the literature; for example, Nijkamp and Blaas (1994) provided a general framework for decision-making in transportation policy planning; Haldenbilen and Ceylan (2005) applied a genetic algorithm to assist policy design with traffic demand estimation; Ü lengin et al (2005) developed a transportation decision support system that uses Bayesian causal map to analyze possible scenarios of transportation policies with long term demand projections; Chan et al (2010) demonstrated the use of advanced optimization techniques in policy decision-making on a simplified tworoad case with constant traffic flow. However many of the previous studies focus on well simplified urban models that are generally unsuitable to the complexities of today's world.…”
Section: Introductionmentioning
confidence: 97%